Patterns of psychotherapy utilisation among women with trauma histories referred to a specialist women’s mental health clinic: A retrospective, cross-sectional study - Georgia Bridgeman; Lakshini Gunasekera; Jayashri Kulkarni (Australasian Psychiatry, 2026)
Objective To describe psychotherapy utilisation patterns, including modality, duration, and subjective satisfaction, among women with trauma histories attending a specialist women’s mental health clinic. Methods Single-centre, retrospective, cross-sectional study of women attending a bulk-billed specialist mental health clinic between January 2016 and June 2025. Demographic and psychotherapy-related data were extracted from clinical records. Data were reported as proportions, with associations assessed using Pearson chi-square tests. Results Of 308 participants, mean age was 40.7 years (SD 11.9). Major depressive disorder was the most common diagnosis (54.6%). Overall, 74.0% had accessed psychotherapy, with non-specific psychotherapy (63.6%) and cognitive behaviour therapy (32.5%) most frequent. Half of those with a psychotherapy history had been engaged in psychotherapy for over 5 years. Most women reported previous trauma (83.8%), significantly associated with psychotherapy use ( p = .013), particularly emotional abuse ( p = .043), and peer bullying ( p = .019). University-level education was also associated with psychotherapy use ( p < .001). Satisfaction was predominantly positive (74.1%), though mixed (15.4%) and negative (10.5%) experiences were reported. Conclusions Psychotherapy was commonly accessed prior to specialist consultation, with most women reporting positive experiences. Findings highlight unmet need for long-term psychotherapy services, gaps in trauma-specific treatment access, and support for policy initiatives expanding psychotherapy delivery.